If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(w + 1) + -1w = 3(w + 1) + 7 Reorder the terms: 5(1 + w) + -1w = 3(w + 1) + 7 (1 * 5 + w * 5) + -1w = 3(w + 1) + 7 (5 + 5w) + -1w = 3(w + 1) + 7 Combine like terms: 5w + -1w = 4w 5 + 4w = 3(w + 1) + 7 Reorder the terms: 5 + 4w = 3(1 + w) + 7 5 + 4w = (1 * 3 + w * 3) + 7 5 + 4w = (3 + 3w) + 7 Reorder the terms: 5 + 4w = 3 + 7 + 3w Combine like terms: 3 + 7 = 10 5 + 4w = 10 + 3w Solving 5 + 4w = 10 + 3w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-3w' to each side of the equation. 5 + 4w + -3w = 10 + 3w + -3w Combine like terms: 4w + -3w = 1w 5 + 1w = 10 + 3w + -3w Combine like terms: 3w + -3w = 0 5 + 1w = 10 + 0 5 + 1w = 10 Add '-5' to each side of the equation. 5 + -5 + 1w = 10 + -5 Combine like terms: 5 + -5 = 0 0 + 1w = 10 + -5 1w = 10 + -5 Combine like terms: 10 + -5 = 5 1w = 5 Divide each side by '1'. w = 5 Simplifying w = 5
| 15x^2/3 | | Xp-qx=n | | [z-3i]+[z+3i]=10 | | -10+2x=x-2 | | -(1-5)=54 | | 1+2t-2t+1+3t=6 | | Y/-65=2 | | 5t(w+1)-w=3(w-1)+7 | | -4x+7=-15-2x | | abs(z-3i)+abs(z+3i)=10 | | 2X^4+4X^3+8X^2+8X+4=0 | | 3000+40.25x=1770+60.75x | | 7x+5=20+2x | | X+5=x+.25x | | (4/5)×=1 | | 4+3x=5x-20 | | 4/5×=1 | | 1+2t-2t+1+3t=10 | | 2x^3-4x^2-20=0 | | y/-65=-6 | | 6/1.75=32/x | | 3x-2(3x+4)=10 | | n+3n=360 | | 90=.7x | | x/0.5=4/11 | | 6/2.875=32/x | | 55=4x+2x+1 | | 15x/3x^3 | | -2x+3=-5x | | 3/2.875=16/x | | -6(x-5)-8=2(x+3) | | 49+.07x=44+.11x |